3D multiphase lattice Boltzmann simulations for morphological effects on self-propelled jumping of droplets on textured superhydrophobic surfaces. (May 2015) - Liu, Xiuliang; Cheng, Ping
Abstract: Coalescence induced droplets self-propelled jumping on textured superhydrophobic surfaces (SHS) is numerically simulated using multiple–relaxation–time (MRT), and three dimensional (3D) multiphase isothermal lattice Boltzmann method. Symmetric boundary conditions and parallel computation with OpenMP algorithm are used to accelerate computational speeds. Simulation results for velocity field show that the downward velocity of the droplet is reverted to upward direction due to the counter action of the wall to the contact base of the droplet during the period of droplet deformation on the texture. For a fixed droplet diameter, the spacing of the microstructure is found to play a key role on jumping velocity of the coalescence droplet, and an optimal spacing of the microstructure exists for a maximum jumping velocity. For a texture with small spacings, the adhesion force due to surface tension is large because of the large contact area which results in a decrease of its jumping velocity. On the other hand, for a texture with large roughness spacings, the lower contour of the droplet will fall into the texture, which will also decrease droplet jumping velocity. Simulation results for jumping velocities are used to explain large differences in measured jumping velocities of small droplets (with radius less than 20 μm) on hierarchical textured and nanostructured surfaces in existing experiments.